2013
DOI: 10.1021/ja402806f
|View full text |Cite
|
Sign up to set email alerts
|

β-Arylation of Carboxamides via Iron-Catalyzed C(sp3)–H Bond Activation

Abstract: A 2,2-disubstituted propionamide bearing an 8-aminoquinolinyl group as the amide moiety can be arylated at the β-methyl position with an organozinc reagent in the presence of an organic oxidant, a catalytic amount of an iron salt, and a biphosphine ligand at 50 °C. Various features of selectivity and reactivity suggest the formation of an organometallic intermediate via rate-determining C-H bond cleavage rather than a free-radical-type reaction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(156 citation statements)
references
References 46 publications
5
142
1
8
Order By: Relevance
“…The asymmetric methods used include the Staudinger ketene-imine [2+2] cycloaddition, Kinugasa alkyne-nitrone cycloaddition, and Gilman-Speeter ester enolate-imine condensation. [1] The seminal work of Daugulis and co-workers on the palladium-catalyzed arylation of secondary C(sp 3 ) À H bonds with an 8-aminoquinoline-derived N,N-bidentate directing group [2] has inspired several research groups to use this type of auxiliary to develop a diverse collection of novel C(sp 3 )ÀH functionalization reactions. [3] Moreover, this chemistry has been applied in the total synthesis of natural products.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The asymmetric methods used include the Staudinger ketene-imine [2+2] cycloaddition, Kinugasa alkyne-nitrone cycloaddition, and Gilman-Speeter ester enolate-imine condensation. [1] The seminal work of Daugulis and co-workers on the palladium-catalyzed arylation of secondary C(sp 3 ) À H bonds with an 8-aminoquinoline-derived N,N-bidentate directing group [2] has inspired several research groups to use this type of auxiliary to develop a diverse collection of novel C(sp 3 )ÀH functionalization reactions. [3] Moreover, this chemistry has been applied in the total synthesis of natural products.…”
mentioning
confidence: 99%
“…[1] The seminal work of Daugulis and co-workers on the palladium-catalyzed arylation of secondary C(sp 3 ) À H bonds with an 8-aminoquinoline-derived N,N-bidentate directing group [2] has inspired several research groups to use this type of auxiliary to develop a diverse collection of novel C(sp 3 )ÀH functionalization reactions. [3] Moreover, this chemistry has been applied in the total synthesis of natural products. [4] Encouraged by these elegant studies, we recently developed a modified bidentate pyridine-containing directing group derived from 2-(pyridin-2-yl)isopropylamine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 In subsequent studies, we explored the use of Ni(0), 27 Ru(II), 28 Ni(II), 29 and Rh(I) 30 complexes as catalysts in C-H functionalizations using a bidentate-chelation system. Other groups also reported that various metals, including Cu(II), 31 Fe(ate), 32 Co(II) 33 complexes could also be used in C-H functionalizations using a N,N¤-bidentate-chelation system. Combinations of transition metal catalysts and N,N-bidentate directing groups have emerged as powerful methods for the construction of carboncarbon and carbon-heteroatom bonds through C-H bond cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Designing a catalyst to meet these requirements continues to be an insurmountable goal, though significant progress has been made. In the 1970s, Shilov and co-workers developed a system using water soluble Pt II salts to C-H activate and functionalize alkanes (Scheme 4); 35,[38][39][40] for example, this system can transform methane to methanol and chloromethane under mild conditions. This process involves methane coordination to a [Pt(Cl) 4 ] 2-salt followed by C-H activation to result in a Pt-Me species.…”
Section: Transition Metal-mediated Partial Oxidation Of Hydrocarbons mentioning
confidence: 99%